Functional High-Intensity Circuit Training Improves Body Composition, Peak Oxygen Uptake, Strength, and Alters Certain Dimensions of Quality of Life in Overweight Women - Sperlich, Billy; Wallmann-Sperlich, Birgit; Zinner, Christoph; Von Stauffenberg, Valerie; Losert, Helena; Holmberg, Hans-Christer (Frontiers in Physiology, 2017)
The effects of circuit-like functional high-intensity training (CircuitHIIT) alone or in combination with high-volume low-intensity exercise (Circuitcombined) on selected cardio-respiratory and metabolic parameters, body composition, functional strength and the quality of life of overweight women were compared. In this single-center, two-armed randomized, controlled study, overweight women performed 9-weeks (3 sessions·wk-1) of either CircuitHIIT (n=11) or Circuitcombined (n= 8). Peak oxygen uptake and perception of physical pain were increased to a greater extent (p < 0.05) by CircuitHIIT, whereas Circuitcombined improved perception of general health more (p < 0.05). Both interventions lowered body mass, body-mass-index, waist-to-hip ratio, fat mass and enhanced fat-free mass; decreased ratings of perceived exertion during submaximal treadmill running; improved the numbers of push-ups, burpees, one-legged squats and 30-s skipping performed, as well as the height of counter-movement jumps; and improved physical and social functioning, role of physical limitations, vitality, role of emotional limitations and mental health to a similar extent (all p < 0.05). Either forms of these multi-stimulating, circuit-like, multiple-joint training can be employed to improve body composition, selected variables of functional strength and certain dimensions of quality of life in overweight women. However, CircuitHIIT improves peak oxygen uptake to a greater extent, but with more perception of pain, whereas Circuitcombined results in better perception of general health.